Hubungan Efikasi Diri, Dukungan Orang Tua, dan Motivasi Berprestasi dengan Prestasi Belajar Fisika Siswa SMAN 1 Giri Banyuwangi - Wulandari, Hildawati; Werang, Basilius Redan; Sulindawati, Ni Luh Gede Erni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to analyze (1) the relationship of self-efficacy with physics learning achievement of SMA Negeri 1 Giri Banyuwangi students, (2) the relationship of parental support with physics learning achievement of SMA Negeri 1 Giri Banyuwangi students, (3) the relationship of achievement motivation with physics learning achievement of SMA Negeri 1 Giri Banyuwangi students, and 4) the relationship of self-efficacy, parental support, and achievement motivation with the achievement of studying physics at SMA Negeri 1 Giri Banyuwangi. This type of research is correlational research with an ex-post-facto research design. The value of the reliability coefficient of self-efficacy questionnaires, parental support, and achievement motivation was 0.809, 0931, and 0.723, respectively, while the students' physics learning achievement test was 0.831. The results of this study showed that 1) there was a positive relationship between self-efficacy and physics learning achievement with an effective contribution of 3.13%, 2) there was a positive relationship between parental support and physics learning achievement with an effective contribution of 61.5%, 3) there was a positive relationship between achievement motivation and physics learning achievement with an effective contribution of 9.29%, and 4) there was a positive relationship between self-efficacy, Parental support, and achievement motivation with physics learning achievement with an effective contribution of 73.92%.